Prolonged complete response to adjuvant tepotinib in a patient with newly diagnosed disseminated glioblastoma harboring mesenchymal-epithelial transition fusion - Pham, Lily C; Weller, Lauryn; Gann, Claudia N; Schumacher, Karl Maria; Vlassak, Soetkin; Swanson, Todd; Highsmith, Kaitlin; O’Brien, Barbara J; Nash, Sebnem; Aaroe, Ashley; de Groot, John F; Majd, Nazanin K (The oncologist (Dayton, Ohio), 2025)
Abstract The prognosis of patients with glioblastoma (GBM) remains poor despite current treatments. Targeted therapy in GBM has been the subject of intense investigation but has not been successful in clinical trials. The reasons for the failure of targeted therapy in GBM are multifold and include a lack of patient selection in trials, the failure to identify driver mutations, and poor blood-brain barrier penetration of investigational drugs. Here, we describe a case of a durable complete response in a newly diagnosed patient with GBM with leptomeningeal dissemination and PTPRZ1-MET fusion who was treated with tepotinib, a brain-penetrant MET inhibitor. This case of successful targeted therapy in a patient with GBM demonstrates that early molecular testing, identification of driver molecular alterations, and treatment with brain-penetrant small molecule inhibitors have the potential to change the outcome in select patients with GBM. This case report of successful targeted therapy in a patient with glioblastoma shows that early molecular testing, identification of driver molecular alterations, and treatment with brain-penetrant small molecule inhibitors have the potential to change the outcome in select patients.